Simultaneous Determination of Paracetamol and Hyoscine-N- Butyl Bromide in Binary Mixture Using Derivative Spectrophotometry and Their Application for Pharmaceutical Samples - Yonis, Marwa S; Al-Saidi, Khaleda H (Al-Nahrain Journal of Science, 2018)
Derivative spectrophotometric (first, second, third and fourth derivative) were used for the determination of paracetamol )PAR) and hyoscine n-butyl bromide (HYO) the binary mixture by applying zero-crossing technique for pure synthetic mixture. Also simultaneous determination of PAR and HYO in (SPAZMOTEK PLUS) tablets was applied. PAR was determined by using 1D and 2D methods at 297.4 and 303.5 nm (zero crossing point of HYO) with linear concentration ranges 2-30 μg.mL-1, with correlation coefficient r (0.9998, 0.9987), LOD (0.081, 0.250 μg mL-1), relative error (0.68, 0.22) and RSD% (0.107, 0.400), respectively. HYO was determined by using 1D method at 215.9 nm (zero crossing point of PAR) with concentration range 2-25 μg mL-1, with correlation coefficient 0.9997 and LOD 0.091μg mL-1, relative error 1.20 and RSD% 0.342. No interference found between both determined and those of matrices. A good accuracy and precision of simultaneous determination of PAR, and HYO were confirmed by statistical analysis. The percentage recovery of the individual drugs under the established conditions is ranged from 95.07% to 100.93%, the proposed procedures were successfully applied to the determination of these compounds in different ratio by synthetic mixtures and pharmaceutical tablets without requiring any separation step.